The leadership illusion : the importance of context and connections - Hall, Tony.; Janman, Karen (Basingstoke : Palgrave MacMillan, 2010)
'This book is about what we have called the'leadership illusion': the hardwired habit of writers, researchers and leaders themselves, when examining success or failure, to focus predominantly on the individual and often the context, but very rarely both. The Leadership Illusion asserts that to make sense of leadership, we have to understand at the same time the context in which leaders operate because both are inextricably interlinked. To try to understand a leader without the context is only half the tale. This book is an attempt to tell the whole story.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Leadership